Late Gastrointestinal Complications of Allogeneic Hematopoietic Stem Cell Transplantation in Adults - Sung, Anthony D. (Biol Blood Marrow Transplant, 2017)
INTRODUCTION: Gastrointestinal (GI) complications including graft versus host disease (GVHD) are a major cause of morbidity and mortality in allogenic stem transplant recipients. While several studies have previously looked into the acute gastrointestinal complications, fewer smaller studies have reported late complications. In this large study, we focus on the late (100 days post-transplant) gastrointestinal complications in allogenic stem transplant recipients METHODS: This is a single center, retrospective study, of all of the adult allogenic stem cell transplant recipients who had their transplant at Duke University over a six year period. A total of 479 patients underwent allogenic stem cell transplant, of whom 392 recipients survived for at least 100 days post-transplant. Late gastrointestinal symptoms were noted in 71 patients, prompting endoscopic evaluation. The primary end point of our study was the diagnosis of GI-GVHD based on endoscopic findings, while overall survival and non-relapse mortality were the secondary end points. RESULTS: Of the 71 patients who underwent endoscopy, 45 (63%) patients had GI-GVHD. Of these 45 patients, 39 (87%) had late acute GVHD, 1 (2%) had chronic GVHD, and 5 (11%) patients had overlap disease. Of the patients who did not have GVHD, the symptoms were mostly related to infectious and inflammatory causes. Less common causes included drug toxicity, food intolerance, disease relapse, and motility issues. In a multivariate analysis, the factors that were most indicative of GI-GVHD were histological findings of apoptosis on the tissue specimen (OR=2.35, 95% CI=1.18 – 4.70, p=0.015) and clinical findings of diarrhea (OR=5.43, 95% CI =1.25 – 23.54, p=0.024). The median survival time from the first endoscopy was 8.5 months. The incidence of non-relapse mortality at 6 months was 31% in patients with GI-GVHD and 19% in patients without GI-GVHD (p=0.42). All the patients with GI-GVHD were on steroid therapy and 31% of them received total parental nutrition. CONCLUSIONS: In our population, close to one-fifth of allogenic transplant recipients experienced late GI complications, warranting endoscopic evaluation. Most of these patients were found to have GI-GVHD which had a high incidence of non-relapse mortality at 6 months and close to one-third of these patients needed total parental nutrition.